1993
DOI: 10.1093/rheumatology/32.4.291
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment and Autoantlbodies in Systemic Lupus Erythematosus

Abstract: Nervous system involvement in systemic lupus erythematosus (SLE) includes a wide array of manifestations some of which have been associated with specific autoantibodies. These include reactivity to surface neuronal and lymphocyte antigens, ribosomal P and cardiolipin. The aim of the present study was to examine the association between cognitive abnormalities and these autoantibodies in an unselected female population of SLE patients. Using a battery of standardized neuropsychological tests, cognitive impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
133
6
11

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(158 citation statements)
references
References 0 publications
8
133
6
11
Order By: Relevance
“…However, these prevalence rates fell to 24% and 4%, respectively, when mild cognitive impairment was excluded. This decision rule for cognitive impairment in SLE patients is similar to that used in a previous study (17), with comparable findings for the prevalence of cognitive impairment in SLE patients and controls. A sensitivity analysis performed in the current study assessing all 19 NP syndromes indicated the profound effect, in terms of frequency, of the use of different decision rules for timing of the onset of the NP event and identifying alternative diagnoses.…”
Section: Discussionsupporting
confidence: 65%
“…However, these prevalence rates fell to 24% and 4%, respectively, when mild cognitive impairment was excluded. This decision rule for cognitive impairment in SLE patients is similar to that used in a previous study (17), with comparable findings for the prevalence of cognitive impairment in SLE patients and controls. A sensitivity analysis performed in the current study assessing all 19 NP syndromes indicated the profound effect, in terms of frequency, of the use of different decision rules for timing of the onset of the NP event and identifying alternative diagnoses.…”
Section: Discussionsupporting
confidence: 65%
“…Cross-sectional studies (1-6) have defined the characteristics of cognitive dysfunction and its prevalence, which has varied from 21% to 66% due t o differences in study populations, the particular neuropsychological tests used, and the definition of cognitive impairment. Most studies have identified subclinical cognitive dysfunction in a substantial proportion of patients (1)(2)(3)(4). It is important to know whether these abnormalities in cognitive function progress over time to more profound cognitive dysfunction or whether they signal the eventual emergence of other clinically overt manifestations of neuropsychiatric SLE (NPSLE).…”
mentioning
confidence: 99%
“…In 1989-1990,70 consecutive SLE patients underwent neuropsychological assessment (2). After a 12-month interval, 59 patients had a repeat assessment (7), and 60 months from the time of the initial assessment, 53 patients were reevaluated.…”
mentioning
confidence: 99%
See 2 more Smart Citations